Konseling Keluarga: Pola Asuh, Childfree, KDRT - Yetti Murniati; Azhariah Fatya; Nurli Hayati; Amelia Rahmi; Hidayani Syam (JURNAL ILMIAH RESEARCH STUDENT, 2025)
The family is the smallest unit in society that plays a crucial role in shaping an individual’s character and personality. However, the family can also be a source of stress and conflict that can affect the mental and emotional well-being of family members. Family problems can arise from various factors, such as differences of opinion, ineffective communication, and changes in family structure. The method used by the researcher in this study is library research. Library research is an effort to collect data and sources on the topic taken in a study. A positive and responsive parenting style can help children grow and develop well. Childfree is a legitimate lifestyle choice for individuals or couples. However, domestic violence is a serious problem that has a negative impact on victims and needs to be addressed seriously through education, legal protection, and support services. The government, society, and family need to work together to create a safe and harmonious environment for all individuals.